A structural atlas of death domain fold proteins reveals their versatile roles in biology and function - Emily J. Wu; Ankita T. Kandalkar; Julian F. Ehrmann; Alexander B. Tong; Jing Zhang; Qian Cong; Hao Wu (Proceedings of the National Academy of Sciences, 2025)
Death domain fold (DDF) superfamily proteins are critically important players in pathways of cell death and inflammation. DDFs are often essential scaffolding domains in receptors, adaptors, or effectors of these pathways by mediating homo- and hetero-oligomerization including helical filament assembly. At the downstream ends of these pathways, effector oligomerization by DDFs brings the enzyme domains into proximity for their dimerization and activation. Hundreds of structures of these domains have been solved. However, a comprehensive understanding of DDFs is lacking. In this article, we report the curation of a DDF structural atlas as a public website (deathdomain.org) and deduce the common and distinct principles of DDF-mediated oligomerization among the four families (death domain or DD, death effector domain or DED, caspase recruitment domain or CARD, and pyrin domain or PYD). We further annotate DDFs genome-wide based on AlphaFold-predicted models and protein sequences. These studies reveal mechanistic rules for this widely distributed domain superfamily.